Efficacy of Nikkomycin Z in the Treatment of Murine Histoplasmosis - Graybill, John R. (American Society for Microbiology, 1998)
Immune-competent ICR and BALB/c athymic (nude) mice were infected intravenously with Histoplasma capsulatum and treated with either fluconazole or nikkomycin Z or 5% dextrose (controls). In immune-competent ICR mice, fluconazole and nikkomycin Z both prolonged survival when given at 5 mg/kg of body weight twice daily. When administered in doses as low as 2.5 mg/kg twice daily, nikkomycin Z reduced fungal counts in both the spleen and liver. When both drugs were combined, there was no antagonism, and in combined therapy spleen and liver counts were reduced more than for either drug alone. However, nikkomycin Z had no effect on brain fungal burden. In nude mice fluconazole and nikkomycin Z had an additive effect in prolongation of survival and reduction of liver and spleen burden. Nikkomycin Z is well tolerated, is at least as effective as fluconazole, and may interact beneficially with fluconazole for treatment of murine histoplasmosis.